Assessing the Resources and Services of Public Libraries for their Conversion Towards community Learning Centres - Javed Iqbal Rana, Rubina Bhatti (IJoLIS, 2024)
Purpose: This study aims to asses whether government public libraries in Punjab (PLsP) have enought resources and services to take up the role of Community Learnng (cLCs) to become proactive organs of the community for livelong learning.